Impact of lateral load on bridge girder - Amira Azura, Jalal (2018)
In this new era globalization, bridge construction has been improved extremely with the advancement in science and technology. However, bridge must be constructed according to the situation and do a regular inspection to validate the safety of bridge and no significant deterioration occurred The main purpose of this innovation is to improve the quality of bridge and reduce risk that might be occurred. As we know, Malaysia had experienced a high rainfall intensity. Usually, flood will be occurred during a Monsoon Season which can cause a serious death and loss of properties. In fact, it can cause of bridge damage and failure when the impact force from flood is too high. According to previous study, bridge submerged in floodwater are subjected to hydrodynamic forces which created by moving of water and also floating debris. There are four types of bridge girder cross section have been used in this test to identify final velocity of water and also pressure that exerted on bridge girder. There are rectangle, trapezoid, inverted trapezoid and hexagon. By doing a simulation on the bridge model, the optimum cross section bridge girder can be determine to improve a bridge that located in flood prone area.